Legislative competition in federal constitutions: a study of the German Basic Law 1949 (قضايا سياسية, 2023)
Federal system establishes for two levels of exercise of power: the level of the federal and the level of the local powers (Cantons, Länder, States). This subject is regulated by the federal constitution, but some of these constitutions predict the occurrence of "conflicts and contradictions" in the exercise of power at the two mentioned levels and therefore include the principle of (legislative competition between the Federation and the Local Federal powers) in order to "contain" these conflicts when they do occur. The principle of legislative competition became a prominent feature In the German Basic Law of 1949, because this principle was able to address an important and dangerous issue that always appears in federal states, which is the issue of “conflict” between the federal authority and the local federal powers that reaches a “dead end” if the Federal Constitution was “oblivious” to the regulation of this issue. The legislators of the Basic Law were aware of this situation and in order to “close” the doors to the emergence of the issue of “conflict”, they included in Articles 72 and 74 what indicates that this conflict should be addressed if it appears in political and constitutional life.The Basic Law succeeded in this task and it constantly and when necessary, made amendments to the above two articles in order to preserve and continue constitutional stability in Germany and thus preserve its political stability.